Machining of light alloys : aluminum, titanium, and magnesium - Carou, Diego; Davim, J. Paulo (Taylor & Francis, a CRC title, part of the Taylor & Francis imprint, a member of the Taylor & Francis Group, the academic division of T & F Informa, plc, 2018)
Light alloys, including aluminum, magnesium, and titanium are used due to their low density which makes them well suited in the manufacturing process when reduction of weight is necessary. Aircrafts, cars, consumable goods, sports equipment, and motorsports applications to name just a few, are what light alloys are used for. The special characteristics of these alloys challenge the knowledge of researchers and the industry in finding the best solutions for machining them in the framework of sustainable manufacturing. This book will provide an understanding of the main problems and issues when machining light alloys.
Keywords: Machining.; Aluminum -- Machinability.; Titanium -- Machinability.; Magnesium -- Machinability.; Light metal alloys.; elektronické knihy; electronic books